SOLAR PLASMA DYNAMICS DURING THE FORMATION AND DEVELOPMENT OF ELLERMAN BOMBS PAIR - Pasechnik, M. N. (Одеські астрономічні публікації, 2019)
The results of the specific features study of solar plasma dynamics in different layers of the active region (AR) of NOAA 11024 under the in- fluence arisen and evolving two Ellerman bombs (EB-1 and EB-2) are presented. Spectral data with high spa- tial and temporal resolution were obtained with the French-Italian THEMIS solar telescope. We used spec- tra were obtained in the H α -line and in the lines form- ing within a wide range of photospheric heights: FeI λ λ 630.15, 630.25, and 630.35 nm and TiI λ 630.38 nm. EBs evolved in the region magnetic flux that were emerging at the time. Changes in the velocity and di- rection of chromospheric and photospheric matter mo- tion in the region of Ellerman bombs and in their im- mediate vicinity at different stages of EBs evolution were determined and analyzed. Temporal variations in the line-of-sight velocities (Vlos) of the chromospheric matter at a level of the H α core formation showed two periods in the velocity en- hancement, containing several individual peaks. The maximum Vlos was –9 and 8 km/s toward and from the observer, respectively. Rapid upward and down- ward plasma streams (where Vlos reaches –80 and 50 km/s, respectively) were sometimes observed. It was found that upflows were predominant at all levels of the AR photosphere. At the same time, Vlos decreased considerably in the region of EBs. Appar- ently, the small-scale downward flows induced by mag- netic reconnections were superimposed onto the large- scale upward motion of the new magnetic flux plasma. The line-of-sight velocity in the central part of EB-1 and EB-2 varied from –1 to 0 km/s and from –1 to 0.2 km/s in the upper photospheric layer and from –1.6 to –0.2 km/s and from –1.1 to 0.25 km/s in the lower layer of the photosphere, respectively. The studied features of temporary changes in the line-of-sight velocities of the chromospheric and photo- spheric matter during the formation and development of Ellerman bombs indicate that they affect both the photosphere and the lower chromosphere.